2020
DOI: 10.3390/ijms21124279
|View full text |Cite|
|
Sign up to set email alerts
|

Early Cellular Responses Induced by Sedimentary Calcite-Processed Particles in Bright Yellow 2 Tobacco Cultured Cells

Abstract: Calcite processed particles (CaPPs, Megagreen®) elaborated from sedimentary limestone rock, and finned by tribomecanic process were found to increase photosynthetic CO2 fixation grapevines and stimulate growth of various cultured plants. Due to their processing, the CaPPs present a jagged shape with some invaginations below the micrometer size. We hypothesised that CaPPs could have a nanoparticle (NP)-like effects on plants. Our data show that CaPPs spontaneously induced reactive oxygen species (ROS) in liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Leaf area retention induced by CaPF significantly increased the leaf area/yield ratio compared to that of not-sprayed in both WW and D vines (Table 3). This beneficial effect might be due to increased ROS, as observed in tobacco (Tran et al, 2020), which, in turn, might have enhanced the vine acclimation response to high air temperature and radiation (Carvalho et al, 2015;Brito et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf area retention induced by CaPF significantly increased the leaf area/yield ratio compared to that of not-sprayed in both WW and D vines (Table 3). This beneficial effect might be due to increased ROS, as observed in tobacco (Tran et al, 2020), which, in turn, might have enhanced the vine acclimation response to high air temperature and radiation (Carvalho et al, 2015;Brito et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bracts and apical meristem sections were prepared as described above. ROS detection was performed by staining with DAB [ 67 , 68 ] (Sigma-Aldrich, Shanghai, China) and HPF [ 69 , 70 ] (Maokang Bio-technology, Shanghai, China). The samples were examined and captured immediately using a ZEISS Axio Imager 2 microscope (Carl Zeiss, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Tran et al investigated the early cellular responses of bright yellow2 tobacco cultured cells under the application of calcite processed particles (CaPPs) [ 14 ]. Their results revealed that CaPPs act such as nanoparticles and induce various signaling pathways.…”
Section: Effects Of Selenium and Sedimentary Calcite-processed Parmentioning
confidence: 99%